2013
DOI: 10.1080/15546128.2012.740893
|View full text |Cite
|
Sign up to set email alerts
|

Examining Behavioral and Psychosocial Predictors of Antibody Testing among College Youth: Implications for HIV Prevention Education and Testing

Abstract: Young adults continue to be disproportionately affected by HIV and AIDS. Despite efforts, antibody testing rates have remained stable. Utilizing a sample of 1,874 students from three universities and seven instruments, this study examined hypothesized demographic, behavioral, and psychosocial predictors of HIV antibody testing. Logistic regression indicated that sexual regulation, depression, attributional style, drug and alcohol use/abuse, HIV knowledge, and sexual risks significantly predicted the likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Scaling up HCT service use in Thailand, the campaign "Early Detection as Treatable" through public media and in schools has promoted favorable attitudes toward HIV testing among the youth (Sirinirund et al, 2012). In addition, previous studies in Thailand have shown that youth who perceived themselves to be at high risk for HIV infection, were more likely to want to know their HIV status and consequently intend to use HCT service (Sabato, Burnett, Kerr, & Wagner, 2013). Our findings also showed that youth who had multiple sex partners and used condoms consistently were more likely to intend to use HCT services.…”
Section: Discussionsupporting
confidence: 68%
“…Scaling up HCT service use in Thailand, the campaign "Early Detection as Treatable" through public media and in schools has promoted favorable attitudes toward HIV testing among the youth (Sirinirund et al, 2012). In addition, previous studies in Thailand have shown that youth who perceived themselves to be at high risk for HIV infection, were more likely to want to know their HIV status and consequently intend to use HCT service (Sabato, Burnett, Kerr, & Wagner, 2013). Our findings also showed that youth who had multiple sex partners and used condoms consistently were more likely to intend to use HCT services.…”
Section: Discussionsupporting
confidence: 68%
“…Twenty articles described research conducted in sub-Saharan Africa [ 34 , 36 38 , 47 – 51 , 54 , 58 , 59 , 62 , 64 , 67 , 76 , 77 , 81 , 85 , 90 ]. Another 21 were conducted in North America [ 32 , 35 , 40 , 42 , 45 , 55 , 57 , 61 , 66 , 68 , 69 , 71 , 73 , 74 , 78 , 80 , 84 , 86 , 87 , 91 , 92 ], one in South America [ 93 ], and four in the Caribbean [ 33 , 82 , 83 , 89 ]. Nine were conducted in Asia [ 39 , 43 , 44 , 46 , 52 , 63 , 65 , 79 , 88 ], five in Europe [ 41 , 53 , 60 , 70 , 72 ], and one in Australia [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…4 items on Likert scale. Adapted [ 170 ] Self-efficacy 10 items on Likert scale From [ 172 ], α = 0.76–0.90 Acceptance of rapid HIV test at time of study HBM constructs Perceived susceptibility to HIV Significant association with testing (AOR 1.13, 1.13–1.27, p = 0.05) Perceived severity Ns (AOR 1.03, 0.86–1.06, p = 0.63) Perceived benefits Ns (AOR 0.95, 0.83–1.17, p = 0.56) Perceived barriers Ns (AOR 1.07, 0.93–1.20, p = 0.36) Self - efficacy Ns (AOR 1.00, 0.95–1.08, p = 0.82) References Location and testing context Design and sampling Measurement of psychological variables Measure of testing behaviour Associations between psychological variables and testing Sabato et al [ 61 ] U.S.A. Students on health courses at selected universities Cross-sectional n = 1874. 552 (29.5 %) males, 1322 (70.5 %) females.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, research has primarily focused on adults in developed countries, singular constructs of SWB, and has only minimally explored SWB in relation to HIV/AIDS (Fako 2006;Sabato et al 2013;Valois et al 2002;Somlai et al 2000;Kalichman et al 1997;Golub et al 2013). One study exploring this relationship found an association between decreased life satisfaction and increased perceived difficulty to perform HIV/AIDS preventive behaviors (delaying sexual intercourse, sex refusal, condom use) among African American adolescents in the U.S. (Valois et al 2015).…”
Section: Introductionmentioning
confidence: 99%